Botulinum Toxin Preoperatory for Oncoplastic Abdominal Wall Resection of Ovarian Metastasis in Rectus Abdominis: Case Report - Aguilar-Barragán, Cuauhtémoc; Sánchez-Ávila, Daniel; Sandoval-Tapia, Sergio; Colchado-Mariscal, Samantha; Ruiz-Berrones, Arianna; Flores-Filio, Jorge (International Journal of Innovative Research in Medical Science, 2024)
Cancers of internal organs is not commonly to metastasize to skin or subcuticular tissue and almost none has been to show metastasis to rectus muscle. We present our preoperative approach with botulinum toxin type A (BTA) and surgical oncoplastic technique to make an abdominal wall block resection in a 55-year-old woman with an ovarian metastasis lesion in rectus abdominis to achieve the closure of aponeurotic midline.